Development of an expert system for sheet-metal-forming die manufacturing methodologies to support an extended design team / Raja Aziz Raja Ma’arof - Raja Ma’arof, Raja Aziz (2006)
In an ever competitive business and manufacturing environment, artificial intelligence (AI) and expert system (ES) play a crucial role in assisting an enterprise to make effective and reliable decisions. This research addresses this issue with the design and development of the architecture of a sheet-metal-forming die manufacturing expert system (DMES) using an up-to-date object-oriented technology (OOT). The DMES method is proposed to improve performance of sheet-metal forming manufacturing activities through the application of concurrent engineering (CE) within an enterprise and collaborative teamwork (CT) amongst industry partners. The knowledge acquisition (KA) of current issues and newfound ideas for improvement on CE and CT is through interviews and discussions with the industry experts. Other specific knowledge is acquired through technical references, resource manuals and on-site data collection. Based on research works by Bugtai and Young (1998) and Zhao, Cheung and Young (1999), the knowledge on die manufacturing is modelled into three components of manufacturing capabilities, namely resource-, process- and strategy-related capabilities (Resource, Process and Strategy respectively). The Resource focuses on the DMES’s physical elements of tool making machines and sheet-metal forming or press machines within an enterprise and industry partners. Process is the action or sequence of actions. Strategy is the restrictions imposed upon the use of manufacturing resources and processes.